Epitaxial Growth of ZnO Films on Patterned c-Plane GaN Layer Using Hydrothermal Method. (7th August 2015) - Ko, Rong-Ming; Lin, Yan-Ru; Wang, Shui-Jinn; Su, Si-Ming; Huang, Yen-Chieh; Yu, Tsung-Hsien
Abstract : The growth of epitaxial ZnO film with a c -axis orientation on a patterned GaN/sapphire substrate using a two-step hydrothermal (HT) process is demonstrated. Honeycomb arrays of etched holes were formed on the GaN epilayer to unveil m -plane for the synthesis of ZnO crystallites with a lattice mismatch of 0.4% along c -axis (as compared with that of 1.88% on the c -plane). Effects of the etched pattern and HT processing parameters on the coalescence of hexagonal ZnO prisms are investigated. Experimental results reveal that etched holes with a 5-μm diameter, 3-μm spacing, and an off angle of 30° between the close-packing direction of the honeycomb array and the a -axis (i.e., the [ 11 2 ̄ 0 ] direction) of GaN yield ZnO films might be most efficient for the ZnO epitaxy. The successful growth of ZnO single-crystalline films can be attributed to the m -plane of GaN providing nucleation sites with a lower lattice mismatch for the hetero-epitaxy of ZnO crystallites and the propagation of homo-epitaxial lateral growth over c - and m -plane. Material analysis results confirm that the continuous ZnO films grown on the GaN epilayer have high quality and a single-crystalline wurtzite structure, suggesting a high potential for use in the fabrication of ZnO substrates and devices.